Microwave-Assisted Carbonization Processing for Carbon Dot-like Nanomaterials with Antimicrobial Properties - Buta Singh; Audrey F. Adcock; Simran Dumra; Jordan Collins; Liju Yang; Christopher E. Bunker; Haijun Qian; Mohammed J. Meziani; Ya-Ping Sun (Micro)
Carbon dots (CDots) are classically defined as small carbon nanoparticles with effective surface passivation, which, in the classical synthesis, has been accomplished by surface organic functionalization. CDot-like nanostructures could also be produced by the thermal carbonization processing of selected organic precursors, in which the non-molecular nanocarbons resulting from the carbonization are embedded in the remaining organic species, which may provide the passivation function for the nanocarbons. In this work, a mixture of oligomeric polyethylenimine and citric acid in the solid state was used for efficient thermal carbonization processing with microwave irradiation under various conditions to produce dot samples with different nanocarbon content. The samples were characterized in terms of their structural and morphological features regarding their similarity or equivalency to those of the classical CDots, along with their significant divergences. Also evaluated were their optical spectroscopic properties and their photoinduced antimicrobial activity against selected bacterial species. The advantages and disadvantages of the thermal carbonization processing method and the resulting dot samples with various features and properties mimicking those of classically synthesized CDots are discussed.